Modified titanium dioxide, preparation method and external preparation for skin
By combining natural film-forming substances with titanium dioxide for double-layer coating, the problems of poor dispersion and rough skin feeling of titanium dioxide are solved, and the skin-fitting properties, makeup-holding effects, moisturizing properties and sun protection properties of cosmetics are improved, and the amount of film-forming agents is reduced.
Patent Information
- Application Number
- CN202411562096.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
AI Technical Summary
Titanium dioxide nude powder has poor dispersion and rough skin. The existing film-forming agents are added in large amounts to cosmetics and have average makeup effect.
By combining natural film-forming substances such as Tremella polysaccharide, Plurandosaccharide and peach gum polysaccharide with titanium dioxide, double-layer coating treatment is carried out to improve the dispersion and fineness of titanium dioxide, and it is applied to skin topical agents.
It improves the skin-adhesiveness, makeup-holding effect, moisturizing performance and sun protection performance of modified titanium dioxide, reduces the amount of film-forming agent added, and improves the skin feeling and the overall performance of the product.
Smart Images

Figure CN119505576A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of skin products, and specifically relates to a modified titanium dioxide, a preparation method and a skin external preparation. Background Art
[0002] Titanium dioxide can be used as a white pigment. It is divided into anatase titanium dioxide and rutile titanium dioxide. Rutile has a high refractive index, high tinting power, strong hiding power, and is relatively stable. It has a strong ability to reflect ultraviolet rays and is widely used in cosmetics. Titanium dioxide is not only a pigment, but also a physical barrier type ultraviolet protection agent with superior performance. It is physiologically inert, has no irritation to the skin, and is extremely safe. However, the bare titanium dioxide has poor dispersibility and a rough skin feel.
[0003] A certain amount of film-forming agent is usually added to base makeup products such as liquid foundation and sunscreen to improve the product's skin adhesion and makeup lasting properties. At the same time, the thin film formed by the film-forming agent on the skin surface can prevent water loss and has a certain moisturizing effect. It can also block a certain amount of ultraviolet rays and improve the product's sun protection performance. However, the demand for film-forming agents added alone to base makeup products is high, and the makeup lasting effect is average. Summary of the invention
[0004] The present application provides a modified titanium dioxide, a preparation method and a skin topical preparation, which combines natural film-forming substances with titanium dioxide to improve the dispersibility and fineness of titanium dioxide. Moreover, its application in skin topical preparations can improve skin adhesion, makeup lasting effect, moisturizing properties and sun protection properties, and reduce the amount of film-forming agent added.
[0005] The first aspect of the present application provides a modified titanium dioxide, which comprises a base material and a coating material located on at least a portion of the surface of the base material; the base material comprises titanium dioxide;
[0006] The coating material comprises a first coating material and a second coating material, wherein the first coating material is arranged between the base material and the second coating material; the first coating material comprises an inorganic material; and the second coating material comprises at least two of tremella polysaccharide, pullulan polysaccharide and peach gum polysaccharide.
[0007] In a feasible implementation manner of the first aspect of the present application, the second coating material includes tremella polysaccharide, pullulan and peach gum polysaccharide in a mass ratio of 1:(0.1-16):(0.25-22), and optionally 1:(1-2):(1-3).
[0008] In a feasible implementation manner of the first aspect of the present application, the mass of the second coating material is 5% to 20% of the mass of the base material.
[0009] In a feasible implementation of the first aspect of the present application, the first coating material includes one or more of aluminum hydroxide, aluminum oxide, silicon dioxide, cerium dioxide and aluminum phosphate; optionally, the mass of the first coating material is 1% to 10% of the mass of the base material.
[0010] In a feasible implementation manner of the first aspect of the present application, the average particle size of the titanium dioxide in the matrix material is 100 nm to 200 nm.
[0011] The second aspect of the present application provides a method for preparing a modified titanium dioxide, comprising:
[0012] Dispersing titanium dioxide in water to obtain a titanium dioxide suspension;
[0013] Adding a weak base salt solution to the titanium dioxide suspension and stirring, adding an alkaline solution to promote the hydrolysis reaction of the weak base salt, and drying to obtain an inorganic material-coated titanium dioxide material;
[0014] Placing an inorganic material-coated titanium dioxide material in water, adding a second coating material, stirring and mixing, and drying to obtain a double-layer coated titanium dioxide, wherein the second coating material comprises at least two of Tremella polysaccharide, pullulan polysaccharide, and peach gum polysaccharide;
[0015] The double-layer coated titanium dioxide is air flow-milled to obtain modified titanium dioxide.
[0016] In a feasible implementation manner of the second aspect of the present application, in the step of dispersing titanium dioxide in water to obtain a titanium dioxide suspension, the concentration of titanium dioxide in the titanium dioxide suspension is 50g / L to 100g / L; the dispersion stirring speed is 800rpm to 100rpm, and the stirring time is 10min to 15min.
[0017] In a feasible implementation manner of the second aspect of the present application, in the steps of adding a weak base salt to a titanium dioxide suspension and stirring, adding an alkaline solution to promote the hydrolysis reaction of the weak base salt, and drying to obtain an inorganic material-coated titanium dioxide material, the weak base salt includes one or more of aluminum sulfate, aluminum chloride and alum; the alkaline solution includes one or more of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate solution, which can be selected from a sodium hydroxide solution with a concentration of 1.2 mol / L to 1.5 mol / L, and the pH value of the alkaline solution can be selected from 9 to 10.
[0018] As in some embodiments of the present application, an aluminum sulfate hydrolysis method is adopted, an aluminum sulfate solution is added to a titanium dioxide dispersion slurry for stirring, and then a sodium hydroxide solution is slowly added to maintain a certain pH value, so that aluminum hydroxide is deposited on the surface of the titanium dioxide, and then reduced pressure filtration, deionized water washing, and vacuum drying are performed to obtain aluminum hydroxide-coated titanium dioxide.
[0019] The number of deionized water washings can be selected to be 3-4 times.
[0020] In a feasible implementation manner of the second aspect of the present application, a weak base salt is added to the titanium dioxide suspension and stirred, an alkaline solution is added to promote the hydrolysis reaction of the weak base salt, and drying is performed to obtain an inorganic material-coated titanium dioxide material. The stirring speed is 2500rpm to 5000rpm, the stirring time is 30min to 45min, and the drying temperature is 80℃ to 110℃.
[0021] In a feasible implementation manner of the second aspect of the present application, an inorganic material-coated titanium dioxide material is placed in water, a second coating material is added and stirred and mixed, and in the step of drying to obtain a double-layer coated titanium dioxide, the stirring and mixing temperature is 50°C to 60°C, optionally, the stirring and mixing speed is 5000rpm to 6000rpm, optionally, the stirring and mixing time is 30min to 45min; the drying temperature is 80°C to 110°C.
[0022] The third aspect of the present application provides a skin topical agent, which includes the modified titanium dioxide in some embodiments of the first aspect of the present application, and the skin topical agent includes liquid foundation, air cushion, primer, sunscreen, liquid concealer, concealer, lipstick, lip glaze, liquid eyeliner, eyeliner pencil, eye shadow, blush or pressed powder.
[0023] In a feasible implementation manner of the third aspect of the present application, the liquid foundation comprises the following components in parts by weight:
[0024] Modified titanium dioxide, 10 parts; and all based on 10 parts of modified titanium dioxide:
[0025] Emulsifier, 0.5-5 parts; oil, 8-30 parts; sunscreen, 5-15 parts; emulsifier, 2-10 parts; thickener, 0.2-2 parts; color powder, 1-5 parts; humectant, 5-20 parts; stabilizer, 0.2-2 parts; preservative, 0.2-2 parts.
[0026] Optionally, the auxiliary emulsifier includes one or more of polyglyceryl-4 isostearate, polyglyceryl-3 diisostearate, polyglyceryl-10 stearate and polyoxyethylene sorbitan fatty acid ester.
[0027] Optionally, the oil includes one or more of cyclopentasiloxane, phenyl trimethicone and C12-15 alcohol benzoate.
[0028] Optionally, the sunscreen includes one or more of ethylhexyl methoxycinnamate, ethylhexyl triazone, diethylaminohydroxybenzoyl hexyl benzoate, butyl methoxydibenzoylmethane, and bis-ethylhexyloxyphenol methoxyphenyl triazine.
[0029] Optionally, the emulsifier includes one or more of cetyl PEG / PPG-10 / 1 dimethicone, PEG-3 dimethicone and PEG-10 dimethicone.
[0030] Optionally, the thickener includes one or more of distearyl dimethylamine hectorite, magnesium aluminum silicate, carbomer and cellulose derivatives.
[0031] Optionally, the color powder includes one or more of titanium dioxide, nano-sized titanium dioxide and iron oxide.
[0032] Optionally, the moisturizer includes one or more of 1,3-butylene glycol, 1,2-hexanediol, glycerol and hyaluronic acid.
[0033] Optionally, the stabilizer includes one or more of magnesium sulfate, sodium chloride, potassium chloride and sodium sulfate.
[0034] Optionally, the preservative includes one or more of phenoxyethanol, sodium benzoate, benzoic acid and potassium sorbate.
[0035] In a feasible implementation manner of the third aspect of the present application, the liquid foundation comprises the following components in parts by weight:
[0036] Modified titanium dioxide, 10 parts; and all based on 10 parts of modified titanium dioxide:
[0037] Polyglyceryl-4 isostearate, 0.5-2 parts; Cyclopentasiloxane, 5-20 parts; Phenyl trimethicone, 1-5 parts; Ethylhexyl methoxycinnamate, 5-20 parts; Cetyl PEG / PPG-10 / 1 polydimethylsiloxane, 2-10 parts; C12-C15 alcohol benzoate, 1-5 parts; Distearyl dimethylamine hectorite, 0.5-2 parts; Nano-titanium dioxide, 0.5-3 parts; Iron oxide, 0.5-3 parts; 1,3-Butanediol, 2-10 parts; Magnesium sulfate, 0.5-2 parts; Phenoxyethanol, 0.5-2 parts; 1,2-Hexanediol, 0.5-2 parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a graph showing the moisturizing performance test results of each formula;
[0039] Figure 2 It is a schematic diagram of the L*a*b color model;
[0040] Figure 3 This is a test result chart of the makeup holding performance of each formula;
[0041] Figure 4 This is a graph of the sunscreen performance test results of each formula;
[0042] Figure 5It is a graph showing the sensory evaluation satisfaction results of each formula. DETAILED DESCRIPTION
[0043] In order to make the invention purpose, technical scheme and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.
[0044] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0045] In the description herein, when a composition is described as containing, comprising or including specific components, or when a process is described as containing, comprising or including specific process steps, it is expected that the composition of the present application also consists essentially of or consists of the components, and the process of the present application also consists essentially of or consists of the process steps.
[0046] The use of the terms "including," "comprising," "containing," and "having" should generally be interpreted as open ended and non-limiting unless expressly stated otherwise.
[0047] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and the “multiple” in “one or more” means more than two.
[0048] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0049] Because bare titanium dioxide has poor dispersibility and a rough skin feel, surface-treated titanium dioxide is increasingly being used. Chemical or physical coating of the titanium dioxide surface using various surface treatment agents and different treatment processes can significantly improve its dispersibility, weather resistance, skin feel and many other properties.
[0050] The film-forming agent modified titanium dioxide currently used in cosmetics is usually derived from chemical synthesis. Although they can improve the product's long-lasting makeup performance to a certain extent, the treated titanium dioxide is not skin-friendly and has a certain sticky and heavy feeling, a rough surface, and a lack of smoothness. At the same time, when used in cosmetics, dryness, powder sticking, and powder floating will occur after makeup is applied. In addition, the treating agent is chemically synthesized and difficult to degrade, which is not very friendly to environmental protection.
[0051] Titanium dioxide treatment methods include surface treatment with triethoxycaprylylsilane, polydimethylsiloxane, phenyl silicone oil, isopropyl titanium triisostearate, fluorosilane, and silicone resin film-forming agent trimethylsiloxysilicate, but the production process is complicated and involves a large amount of organic solvents, coupling agents, and catalysts such as strong acids. These substances can cause certain pollution to the environment and need to be treated in subsequent processes.
[0052] Compared with chemically synthesized film-forming agents, natural components usually come from plants, fungi, etc. After being treated with them, titanium dioxide has the advantages of good skin-friendly effect, certain moisturizing properties, and good biodegradability. However, if it is not handled properly, the improvement effect is not good, and it is easy to cause poor makeup durability. For example, although some natural film-forming compositions are used in base makeup products, the added amount is high, the film is large, and the product will increase its stickiness. For example, some film-forming agents are in high demand when added to base makeup products alone, but the makeup durability is average.
[0053] The present application provides a modified titanium dioxide, a preparation method and a skin topical preparation, which combines natural film-forming substances with titanium dioxide to improve the dispersibility and fineness of titanium dioxide. Moreover, its application in skin topical preparations can improve skin adhesion, makeup lasting effect, moisturizing properties and sun protection properties, and reduce the amount of film-forming agent added.
[0054] In the first aspect of the present application, a modified titanium dioxide is provided, wherein the modified titanium dioxide comprises a base material and a coating material located on at least a portion of the surface of the base material; the base material comprises titanium dioxide;
[0055] The coating material comprises a first coating material and a second coating material, wherein the first coating material is arranged between the base material and the second coating material; the first coating material comprises an inorganic material; and the second coating material comprises at least two of tremella polysaccharide, pullulan polysaccharide and peach gum polysaccharide.
[0056] The present application performs a double-layer coating on titanium dioxide. A layer of inorganic material such as aluminum hydroxide is first coated on the surface of the base material titanium dioxide, which can make the titanium dioxide more hydrophilic, while slowing down its aggregation and enhancing its dispersion performance, which is conducive to the titanium dioxide being more easily dispersed in water during the subsequent coating process, so that the second layer of coating material such as a natural film-forming agent composition can better coat the surface thereof.
[0057] On the basis of one layer of coating, the present application uses at least two of the natural film-forming agents Tremella polysaccharide, pullulan polysaccharide and peach gum polysaccharide with good water-resistant and oil-resistant properties as the second layer of coating materials, and better combines the natural film-forming agent with titanium dioxide. The film formed by the polysaccharide composition is better coated on the titanium dioxide, so that the titanium dioxide has good biocompatibility, is mild and non-irritating, and has good film-forming properties, which improves the skin-fitting property of the powder and can also absorb moisture in the air to achieve a moisturizing effect. It can also improve the makeup durability of the titanium dioxide modified by the natural source treatment agent. The film formed on the surface can also resist certain ultraviolet rays, so that the sunscreen performance of the powder is improved to a certain extent. Compared with other surface-treated titanium dioxide, such as silicone-treated titanium dioxide, the modified titanium dioxide of the present application can be used in products to improve the problems of stickiness and heaviness, rough surface, lack of smoothness, dryness, floating powder, etc.
[0058] In addition, the present application uses the natural film-forming substance composition as the second coating material to better coat the surface of titanium dioxide, which can reduce the amount of film-forming agent used in skin external preparations and reduce the sticky feeling of the skin.
[0059] As in some embodiments of the present application, modified titanium dioxide is applied to liquid foundation. Based on the total mass of the liquid foundation as 100%, the added amount of modified titanium dioxide can be 5% to 15%, of which the natural film-forming substance composition can be 5% to 20% of the added amount of modified titanium dioxide, that is, the added amount of natural film-forming substance can be 0.25% to 3%, which is a relatively low amount.
[0060] In some embodiments, the second coating material includes Tremella fuciformis polysaccharide, pullulan polysaccharide and peach gum polysaccharide in a mass ratio of 1:(0.1-16):(0.25-22), or optionally 1:(1-2):(1-3).
[0061] Tremella polysaccharide is a polysaccharide component extracted from Tremella fruiting bodies, pullulan is an extracellular water-soluble macromolecular mucopolysaccharide similar to dextran and xanthan gum produced by fermentation of budding Aureobasidium pullulans, and peach gum polysaccharide is a polysaccharide component extracted from the colloid secreted by plants of the Rosaceae family. They all have good biocompatibility and hygroscopicity, excellent moisturizing effect, are gentle on the skin, and can repair the skin. They are macromolecular polymers with a unique spatial network structure. Their aqueous solutions have strong viscoelasticity and lubricity. When applied to the skin surface, they can form a moisturizing and breathable film to keep the skin shiny and smooth.
[0062] Macromolecular polysaccharides can form a "barrier" on the surface of the skin or mucous membrane, which can prevent the skin from evaporating water and protect the skin from harmful external invasion. Tremella polysaccharide film is white and slightly transparent. After absorbing moisture and softening, the film is elastic and stretchable, and the film-forming effect is good; pullulan polysaccharide film is transparent and has good film-forming properties; peach gum polysaccharide film is transparent yellow-brown. After absorbing moisture and softening, the film is elastic and stretchable, and the film-forming effect is good. They can form a continuous sugar film after absorbing moisture. Therefore, although they have a certain degree of water solubility, they have good water and sebum resistance after film formation.
[0063] Tremella polysaccharide, pullulan and peach gum polysaccharide have excellent film-forming effects, but there are certain differences in film performance. The tensile strength of Tremella polysaccharide film is the largest, but the stretchability is weaker than that of peach gum polysaccharide film, and the tight feeling after applying makeup in liquid foundation will be slightly stronger, while the good stretchability of peach gum polysaccharide can make it more skin-friendly and flexible. Pullulan is more brittle after film formation, and its tensile performance is weaker. It is easy to crack after film formation, lacks flexibility, but has good anti-scratch and anti-migration performance, low stickiness, and is more refreshing. In some embodiments of the present application, after Tremella polysaccharide, pullulan and peach gum polysaccharide are combined, titanium dioxide is surface-modified and applied to base makeup products, which can achieve better makeup-lasting effect and improve skin feel.
[0064] In some embodiments, the mass of the second coating material is 5% to 20% of the mass of the base material.
[0065] In some embodiments, the first coating material includes one or more of aluminum hydroxide, aluminum oxide, silicon dioxide, cerium dioxide and aluminum phosphate; optionally, the mass of the first coating material is 1% to 10% of the mass of the base material.
[0066] In some embodiments, the average particle size of the titanium dioxide in the matrix material is 100 nm to 200 nm.
[0067] In some embodiments of the present application, the titanium dioxide particle size within this range has better dispersibility and covering properties, and also has a better skin feel.
[0068] In the second aspect of the present application, a method for preparing a modified titanium dioxide is provided, comprising:
[0069] Dispersing titanium dioxide in water to obtain a titanium dioxide suspension;
[0070] Adding a weak base salt solution to the titanium dioxide suspension and stirring, adding an alkaline solution to promote the hydrolysis reaction of the weak base salt, and drying to obtain an inorganic material-coated titanium dioxide material;
[0071] Placing an inorganic material-coated titanium dioxide material in water, adding a second coating material, stirring and mixing, and drying to obtain a double-layer coated titanium dioxide, wherein the second coating material comprises at least two of Tremella polysaccharide, pullulan polysaccharide, and peach gum polysaccharide;
[0072] The double-layer coated titanium dioxide is air flow-milled to obtain modified titanium dioxide.
[0073] The process of surface coating titanium dioxide in the present invention is simple and can be directly carried out in an aqueous phase without using a large amount of organic solvents, coupling agents, catalysts, etc. The post-processing is simple and almost no pollution is caused to the environment.
[0074] The air flow crushing in the present application utilizes the interaction between high-speed airflow and material particles, and can achieve efficient crushing in a short time. It can make the powder particle size of the titanium dioxide after encapsulation uniform, prevent the powder from agglomerating again, and make it better dispersed in the cosmetic formula system, with better makeup holding, moisturizing and sun protection performance.
[0075] In some embodiments, in the step of dispersing titanium dioxide in water to obtain a titanium dioxide suspension, the concentration of titanium dioxide in the titanium dioxide suspension is 50 g / L to 100 g / L; the stirring speed of the dispersion is 800 rpm to 100 rpm, and the stirring time is 10 min to 15 min.
[0076] In some embodiments, in the steps of adding a weak base salt to a titanium dioxide suspension and stirring, adding an alkaline solution to promote the hydrolysis reaction of the weak base salt, and drying to obtain an inorganic material-coated titanium dioxide material, the weak base salt includes one or more of aluminum sulfate, aluminum chloride and alum; the alkaline solution includes one or more of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate solution, which can be selected from a sodium hydroxide solution with a concentration of 1.2 mol / L to 1.5 mol / L, and the pH value of the alkaline solution can be selected from 9 to 10.
[0077] As in some embodiments of the present application, an aluminum sulfate hydrolysis method is adopted, an aluminum sulfate solution is added to a titanium dioxide dispersion slurry for stirring, and then a sodium hydroxide solution is slowly added to maintain a certain pH value, so that aluminum hydroxide is deposited on the surface of the titanium dioxide, and then reduced pressure filtration, deionized water washing, and vacuum drying are performed to obtain aluminum hydroxide-coated titanium dioxide.
[0078] The aluminum hydroxide coated titanium dioxide has good hydrophilicity and can slow down its aggregation and enhance its dispersion performance, so that it can be better dispersed in water and coated in the subsequent encapsulation step.
[0079] A pH value in the range of 9-10 can better hydrolyze aluminum sulfate, allowing aluminum hydroxide to precipitate on the surface of titanium dioxide, while facilitating subsequent purification treatment.
[0080] The number of deionized water washings can be selected to be 3-4 times, which can remove excess soluble salts and alkaline solvents.
[0081] In some embodiments, a weak base salt is added to a titanium dioxide suspension and stirred, an alkaline solution is added to promote the hydrolysis reaction of the weak base salt, and drying is performed to obtain an inorganic material-coated titanium dioxide material. The stirring speed is 2500 rpm to 5000 rpm, the stirring time is 30 min to 45 min, and the drying temperature is 80°C to 110°C.
[0082] In some embodiments, an inorganic material-coated titanium dioxide material is placed in water, a second coating material is added and stirred and mixed, and then dried to obtain a double-layer coated titanium dioxide. The stirring and mixing temperature is 50°C to 60°C, and optionally, the stirring and mixing speed is 5000rpm to 6000rpm. Optionally, the stirring and mixing time is 30min to 45min; the drying temperature is 80°C to 110°C.
[0083] In some embodiments, Tremella polysaccharide, pullulan polysaccharide, and peach gum polysaccharide are all purified powders and can be purchased from Shanghai Huiwen Biotechnology Co., Ltd.
[0084] During the high-speed stirring mixing process, the natural film-forming agent composition powder can be well dissolved in water and evenly distributed at 50-60°C, wherein the aluminum hydroxide coated titanium dioxide is used as the matrix, and then the mechanical forces such as extrusion, impact, shearing, and friction generated during the high-speed stirring process cause hydrogen bonding, intermolecular forces, adsorption forces, adhesion forces, and other forces to be generated between the matrix and the coating agent natural film-forming agent composition, and the coating agent is coated on the surface of the aluminum hydroxide coated titanium dioxide in the form of a continuous film through the corresponding forces. It is not necessary to use a large amount of organic solvents, coupling agents, catalysts such as strong acids, etc., and avoid removal during subsequent treatment, which will cause certain pollution to the environment.
[0085] In the above steps, after stirring and mixing, the mixture is further filtered under reduced pressure, washed with deionized water, and dried under vacuum. The number of deionized water washing is preferably 3-4 times, so as to remove the excess natural film-forming agent composition that has not been coated, and the natural film-forming agent composition that has not been coated can be returned to the coating step for recycling.
[0086] In an embodiment of the third aspect of the present application, a skin topical preparation is provided, which includes the modified titanium dioxide in some embodiments of the first aspect of the present application, and the skin topical preparation includes liquid foundation, air cushion, primer, sunscreen, liquid concealer, concealer, lipstick, lip glaze, liquid eyeliner, eyeliner pencil, eye shadow, blush or pressed powder.
[0087] In some embodiments, the liquid foundation comprises the following components in parts by weight:
[0088] Modified titanium dioxide, 10 parts; and all based on 10 parts of modified titanium dioxide:
[0089] Emulsifier, 0.5-5 parts; oil, 8-30 parts; sunscreen, 5-15 parts; emulsifier, 2-10 parts; thickener, 0.2-2 parts; color powder, 1-5 parts; humectant, 5-20 parts; stabilizer, 0.2-2 parts; preservative, 0.2-2 parts.
[0090] Optionally, the auxiliary emulsifier includes one or more of polyglyceryl-4 isostearate, polyglyceryl-3 diisostearate, polyglyceryl-10 stearate and polyoxyethylene sorbitan fatty acid ester.
[0091] Optionally, the oil includes one or more of cyclopentasiloxane, phenyl trimethicone and C12-15 alcohol benzoate.
[0092] Optionally, the sunscreen includes one or more of ethylhexyl methoxycinnamate, ethylhexyl triazone, diethylaminohydroxybenzoyl hexyl benzoate, butyl methoxydibenzoylmethane, and bis-ethylhexyloxyphenol methoxyphenyl triazine.
[0093] Optionally, the emulsifier includes one or more of cetyl PEG / PPG-10 / 1 dimethicone, PEG-3 dimethicone and PEG-10 dimethicone.
[0094] Optionally, the thickener includes one or more of distearyl dimethylamine hectorite, magnesium aluminum silicate, carbomer and cellulose derivatives.
[0095] Optionally, the color powder includes one or more of titanium dioxide, nano-sized titanium dioxide and iron oxide.
[0096] Optionally, the moisturizer includes one or more of 1,3-butylene glycol, 1,2-hexanediol, glycerol and hyaluronic acid.
[0097] Optionally, the stabilizer includes one or more of magnesium sulfate, sodium chloride, potassium chloride and sodium sulfate.
[0098] Optionally, the preservative includes one or more of phenoxyethanol, sodium benzoate, benzoic acid and potassium sorbate.
[0099] In some embodiments, the liquid foundation comprises the following components in parts by weight:
[0100] Modified titanium dioxide, 10 parts; and all based on 10 parts of modified titanium dioxide:
[0101] Polyglyceryl-4 isostearate, 0.5-2 parts; Cyclopentasiloxane, 5-20 parts; Phenyl trimethicone, 1-5 parts; Ethylhexyl methoxycinnamate, 5-20 parts; Cetyl PEG / PPG-10 / 1 polydimethylsiloxane, 2-10 parts; C12-C 15 alcohol benzoate, 1-5 parts; Distearyl dimethylamine hectorite, 0.5-2 parts; Titanium dioxide, 0.5-3 parts; Iron oxide, 0.5-3 parts; 1,3-Butanediol, 2-10 parts; Magnesium sulfate, 0.5-2 parts; Phenoxyethanol, 0.5-2 parts; 1,2-Hexanediol, 0.5-2 parts.
[0102] Example
[0103] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0104] Tremella polysaccharide, pullulan polysaccharide and peach gum polysaccharide were all purified powders purchased from Shanghai Huiwen Biotechnology Co., Ltd.
[0105] Example 1
[0106] The preparation of the modified titanium dioxide in this embodiment includes:
[0107] Bare powder dispersion: add 100g titanium dioxide (average particle size of 150nm) into 1L deionized water for dispersion, and stir with a stirrer at 1000rpm for 15min to obtain titanium dioxide dispersion slurry.
[0108] For inorganic coating, 10 ml of 1 mol / L aluminum sulfate solution was added to the titanium dioxide dispersion and stirred at 3000 rpm for 3 min, and then 1.5 mol / L sodium hydroxide solution was slowly added to maintain the pH value of the whole system at 9-10. Finally, it was stirred at 5000 rpm for 45 min to allow aluminum hydroxide to be deposited on the surface of the titanium dioxide sodium hydroxide solution. Then, it was filtered under reduced pressure, washed with deionized water 3 times, and vacuum dried at 100°C until the moisture content was less than 3%, to obtain aluminum hydroxide-coated titanium dioxide.
[0109] The natural film-forming agent composition is coated, and the aluminum hydroxide-coated titanium dioxide obtained in the inorganic coating step is added to 1L of deionized water for dispersion, and stirred with a stirrer at 1000rpm for 10min to mix evenly, and then 5g of tremella polysaccharide, 5g of pullulan and 5g of peach gum polysaccharide (mass ratio is 1:1:1, and the total coating amount is 15% of the base material) are slowly added, and stirred and mixed at 6000rpm for 45min at 60°C, so that the natural film-forming agent composition is coated on the surface of the aluminum hydroxide-coated titanium dioxide, and then reduced pressure filtration is performed, deionized water washing is performed 3 times, and vacuum drying is performed at 100°C to constant weight.
[0110] Airflow pulverization: adding the titanium dioxide powder vacuum-dried in the natural film-forming agent composition coating step into an airflow pulverizer for airflow pulverization to obtain natural film-forming agent composition modified titanium dioxide powder.
[0111] The modified titanium dioxide obtained in this example is marked as C1.
[0112] Example 2
[0113] The difference between this embodiment and embodiment 1 is that 3 g of Tremella polysaccharide, 6 g of pullulan polysaccharide, and 6 g of peach gum polysaccharide are added in step three, and the mass ratio is 1:2:2.
[0114] The modified titanium dioxide obtained in this example is marked as C2.
[0115] Example 3
[0116] The difference between this embodiment and embodiment 1 is that 2.5 g of Tremella polysaccharide, 5 g of pullulan polysaccharide, and 7.5 g of peach gum polysaccharide are added in step three, and the mass ratio is 1:2:3.
[0117] The modified titanium dioxide obtained in this example is marked as C3.
[0118] Comparative Example 1
[0119] The difference between this comparative example and Example 1 is that the aluminum hydroxide coating pretreatment is not performed on the titanium dioxide, and the natural film-forming agent composition coating treatment is performed directly.
[0120] The modified titanium dioxide obtained in this comparative example is marked as D1.
[0121] Comparative Example 2
[0122] The difference between this embodiment and embodiment 1 is that only 15 g of Tremella polysaccharide is added in step three.
[0123] The modified titanium dioxide obtained in this comparative example is marked as D2.
[0124] Comparative Example 3
[0125] The difference between this embodiment and embodiment 1 is that only 15 g of pullulan is added in step three.
[0126] The modified titanium dioxide obtained in this comparative example is marked as D3.
[0127] Comparative Example 4
[0128] The difference between this comparative example and Example 1 is that only 15 g of peach gum polysaccharide is added in step three.
[0129] The modified titanium dioxide obtained in this comparative example is marked as D4.
[0130] Comparative Example 5
[0131] The difference between this comparative example and Example 1 is that no airflow pulverization is performed at the end.
[0132] The modified titanium dioxide obtained in this comparative example is marked as D5.
[0133] The products obtained in the examples and comparative examples were compared with commercially available products. The most representative commercial products selected were titanium dioxide treated with triethoxycaprylylsilane, disodium stearoyl glutamate and trimethylsiloxysilicate. The main difference was that the outermost coating materials were different. Among them, titanium dioxide treated with triethoxycaprylylsilane was purchased from Buer Fine Chemicals (Shanghai) Co., Ltd., titanium dioxide treated with disodium stearoyl glutamate was purchased from Sanhao Cosmetics Materials (Suzhou) Co., Ltd., and titanium dioxide treated with trimethylsiloxane was purchased from Shanghai Koufeng Biotechnology Co., Ltd.
[0134] The products obtained in the examples and comparative examples and the commercially available products were added with the same content and applied to the same foundation liquid basic formula for performance testing, and the specific steps were as follows:
[0135] The commercially available titanium dioxide treated with triethoxycaprylylsilane, disodium stearoyl glutamate and trimethylsiloxane were marked as E1, E2 and E3, respectively.
[0136] The preparation process of liquid foundation is as follows:
[0137] Add the raw materials of phase B in formula 1-formula 11 to the water phase pot in sequence, stir at 2000rpm for 5 minutes, and heat to 75℃ and keep warm. Add the raw materials in phase A to the emulsification pot in sequence, heat to 75℃ and homogenize at 5000rpm for 10 minutes until completely dispersed. While phase A is stirring at 2000rpm, slowly draw phase B from the water phase pot into the emulsification pot and homogenize at 5000rpm for 10 minutes. Continue stirring and cool to below 40℃. After the physical and chemical indicators are tested to be qualified, the material can be filtered out.
[0138] Specifically, the components and ratios in each foundation liquid are shown in Table 1.
[0139] Test Section
[0140] The foundation liquids obtained from the above 11 formulas were subjected to performance tests, and the test items included moisturizing, makeup lasting, sun protection performance, and sensory evaluation tests.
[0141] 1. Moisturizing performance test
[0142] This moisturizing performance test uses samples made from the above formulas 1-11 to conduct makeup tests on human faces. Three dry skin subjects are selected for each formula for parallel tests. The water content of the skin stratum corneum in the same area of the skin is tested before makeup, 4 hours and 8 hours after makeup, and the water content of the skin stratum corneum before makeup is used as the benchmark (100%). The water change rate of the skin stratum corneum after 4 hours and 8 hours of makeup is calculated, and the test results are all averaged. The moisturizing performance tests are all tested under the same environmental conditions, with the temperature maintained at 25°C and the humidity maintained at about 50%. The test method adopts the CORNEOMETER-capacitance method, and the test instrument is the Corneometer CM825 skin moisture tester.
[0143] 2. Makeup lasting performance test
[0144] The makeup lasting performance test used samples made from the above formulas 1-11 to conduct makeup tests on human faces. Three dry skin subjects were selected for parallel tests for each formula. The skin pigmentation analyzer Antera 3D was used to test the L, a, and b values of the same area of the skin before makeup, 4 hours and 8 hours after makeup. The L, a, and b values before makeup were used as the reference, and the color difference value △E was calculated 4 hours and 8 hours after makeup. The test results were all averaged, where ΔE=, the larger the ΔE, the more obvious the color change and the worse the makeup lasting performance. Conversely, the smaller the ΔE, the smaller the color change and the better the makeup lasting performance. △L is the "lightness difference", and the value from negative to positive represents from dark to light; Δa and Δb are the "color difference", and the a value from negative to positive represents the color change from green to red, and the b value from negative to positive represents the color change from blue to yellow. Figure 2 This is the L*a*b color model. The picture was obtained through public channels on the Internet and is only displayed as a schematic model. The makeup lasting performance tests were all conducted under the same environmental conditions, with the temperature maintained at 25°C and the humidity maintained at around 50%.
[0145] 3. Sunscreen performance test
[0146] The sunscreen performance test uses the UV-2000S cosmetic UV transmittance tester from Labsphere (Lapisphere Optics) in the United States. Its principle is to detect the transmittance of ultraviolet light to sunscreen products, and can quickly measure the transmittance of sunscreen samples in the 250-450nm UV band. The test method refers to the ISO 24443:2021 in vitro sunscreen test method. The samples prepared by formulas 1-11 are evenly applied on the PMMA board, and the in vitro SPF value is tested using Labsphere's UV-2000S. Each formula sample is tested 3 times and the average value is taken.
[0147] 4. Sensory evaluation test
[0148] Sensory evaluation test 15 consumers were randomly selected for blind test, and the foundation samples prepared by formula 1-11 were applied in the same amount on the arm in an area of 2×4cm. The sensory evaluation test was conducted under the same environmental conditions, with the temperature maintained at 25℃ and the humidity maintained at about 50%. The subjects gave feedback on the results of self-evaluation, and each person scored on a 1-10 point scale. The satisfaction calculation formula is as follows: Satisfaction = total evaluation score / (10*number of people)*100%.
[0149] The above test results are shown in Table 2 and Figures 1 to 5 .
[0150]
[0151]
[0152]
[0153] As can be seen from Tables 1 and 2: The test results of the moisturizing performance test are shown in Tables 2 and Figure 1As shown, the moisturizing performance of liquid foundation formula 1 4h and 8h after application is better than that of formula 4 and formula 8, indicating that titanium dioxide pretreated with aluminum hydroxide and then modified with a natural film-forming agent composition or modified with a natural film-forming agent composition and then air flow crushed and applied to liquid foundation can be better spread on the skin for moisturizing, thereby improving the moisturizing performance of the product. The moisturizing properties of foundation formulas 1-8 with titanium dioxide modified with natural film-forming agents 4h and 8h after application are better than those of foundation formula 9 with titanium dioxide modified with triethoxyoctylsilane, foundation formula 10 with titanium dioxide treated with disodium stearoyl glutamate, and foundation formula 11 with titanium dioxide treated with trimethylsiloxysilicate. Among them, foundation formulas 1-3 contain titanium dioxide modified with a natural film-forming agent combination, and their moisturizing properties after application are better than those of foundation formulas 5-7 with titanium dioxide modified with a single natural film-forming agent. This indicates that the present application uses a natural film-forming agent combination to treat the surface of titanium dioxide and then apply it to the foundation, which can better improve the moisturizing properties of the product, and the moisturizing properties of the foundation (formula 1) containing a surface-modified titanium dioxide composed of 5 parts of tremella polysaccharide, 5 parts of pullulan polysaccharide, and 5 parts of peach gum polysaccharide are even better.
[0154] The test results of makeup holding performance are shown in Table 2 and Figure 3 As shown, the lasting performance of liquid foundation formula 1 4h and 8h after application is better than that of formula 4 and formula 8, indicating that titanium dioxide pre-treated with aluminum hydroxide and then modified with a natural film-forming agent composition or modified with a natural film-forming agent composition and then airflow crushed and applied to liquid foundation can improve the lasting performance of the product. The lasting performance of liquid foundation formulas 1-8 containing titanium dioxide modified with natural film-forming agents at 4h and 8h after application is better than that of liquid foundation formula 9 containing titanium dioxide modified with triethoxyoctylsilane and liquid foundation formula 10 containing titanium dioxide treated with disodium stearoyl glutamate. Among them, the lasting performance of liquid foundation formulas 1-3 containing titanium dioxide modified with a natural film-forming agent combination is better than that of liquid foundation formulas 5-7 containing titanium dioxide modified with a single natural film-forming agent. This shows that the application uses the natural film-forming agent combination to treat the surface of titanium dioxide and then apply it to the liquid foundation, which can better improve the lasting performance of the product, and the lasting performance of the liquid foundation (formula 1) containing a surface-modified titanium dioxide composed of 5 parts of tremella polysaccharide, 5 parts of pullulan polysaccharide and 5 parts of peach gum polysaccharide is even better.
[0155] The sun protection performance test results are shown in Table 2 and Figure 4As shown, the sun protection performance of liquid foundation formula 1 is better than that of formula 4 and formula 8, indicating that titanium dioxide can improve the sun protection performance of the product by being pretreated with aluminum hydroxide and then modified with a natural film-forming agent composition or by being modified with a natural film-forming agent composition and then air flow crushing and applied to liquid foundation. The sunscreen performance of liquid foundation formulas 1-8 with titanium dioxide modified with natural film-forming agents is better than that of liquid foundation formula 9 with titanium dioxide modified with triethoxyoctylsilane and liquid foundation formula 10 with titanium dioxide treated with disodium stearoyl glutamate. Among them, the sunscreen performance of liquid foundation formulas 1-3 containing titanium dioxide modified with a natural film-forming agent combination is better than that of liquid foundation formulas 5-7 with titanium dioxide modified with a single natural film-forming agent. This shows that the present application uses a natural film-forming agent combination to treat the surface of titanium dioxide and then apply it to the liquid foundation, which can better improve the sunscreen performance of the product. In addition, the liquid foundation (formula 1) containing titanium dioxide surface modified with a combination of 5 parts of tremella polysaccharide, 5 parts of pullulan polysaccharide and 5 parts of peach gum polysaccharide has even better sunscreen performance, which is significantly higher than the liquid foundation (formula 11) containing titanium dioxide treated with a chemically synthesized film-forming agent trimethylsiloxane.
[0156] The sensory evaluation test results are shown in Table 2 and Figure 5 As shown, from the multi-dimensional satisfaction data in the chart, it can be seen that the extensibility, freshness, skin-fitting, powder-free degree, fineness, moisturizing, and smoothness after drying of liquid foundation formula 1 are better than those of formula 4 and formula 8, indicating that titanium dioxide is pre-treated with aluminum hydroxide and then modified with a natural film-forming agent composition, or modified with a natural film-forming agent composition and then subjected to air flow grinding and applied to liquid foundation, which can improve the sensory evaluation indicators of the product. The freshness, smoothness after drying, extensibility, powder-free degree, and moisturizing of liquid foundation formulas 1-8 with titanium dioxide modified with natural film-forming agents are far better than those of the liquid foundation containing titanium dioxide treated with trimethylsiloxane, a film-forming agent of chemical synthesis origin (formula 11). Among them, the satisfaction of each dimension of the sensory evaluation of liquid foundation formulas 1-3 containing titanium dioxide modified with a natural film-forming agent composition is better than that of liquid foundation formulas 5-7 with titanium dioxide modified with a single natural film-forming agent, indicating that the present application will The natural film-forming agent combination is used in liquid foundation to treat the surface of titanium dioxide, which can better improve the sensory performance of the product. In all dimensions, it is better than the liquid foundation formula 9 with triethoxycaprylylsilane modified titanium dioxide and the liquid foundation formula 10 with disodium stearoyl glutamate treated titanium dioxide. The liquid foundation (formula 1) with a surface modified titanium dioxide containing 5 parts of tremella polysaccharide, 5 parts of pullulan polysaccharide, and 5 parts of peach gum polysaccharide is relatively superior in all dimensions of sensory performance.
[0157] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A modified titanium dioxide, characterized in that: The modified titanium dioxide comprises a base material and a coating material located on at least a portion of the surface of the base material; the base material comprises titanium dioxide; The coating material includes a first coating material and a second coating material, wherein the first coating material is arranged between the base material and the second coating material; the first coating material includes an inorganic material; and the second coating material includes at least two of tremella polysaccharide, pullulan polysaccharide and peach gum polysaccharide.
2. The modified titanium dioxide according to claim 1, characterized in that The second coating material includes Tremella polysaccharide, pullulan and peach gum polysaccharide in a mass ratio of 1:(0.1-16):(0.25-22), and optionally 1:(1-2):(1-3).
3. The modified titanium dioxide according to claim 1, characterized in that The mass of the second coating material is 5% to 20% of the mass of the base material.
4. The modified titanium dioxide according to claim 1, characterized in that The first coating material includes one or more of aluminum hydroxide, aluminum oxide, silicon dioxide, cerium dioxide and aluminum phosphate; optionally, the mass of the first coating material is 1% to 10% of the mass of the base material.
5. The modified titanium dioxide according to claim 1, characterized in that: The average particle size of the titanium dioxide in the matrix material is 100nm to 200nm.
6. A method for preparing modified titanium dioxide, characterized in that: include: Dispersing titanium dioxide in water to obtain a titanium dioxide suspension; Adding a weak base salt solution to the titanium dioxide suspension and stirring, adding an alkaline solution to promote a hydrolysis reaction of the weak base salt, and drying to obtain an inorganic material-coated titanium dioxide material; The inorganic material coated titanium dioxide material is placed in water, a second coating material is added, stirred and mixed, and dried to obtain a double-layer coated titanium dioxide, wherein the second coating material includes at least two of Tremella polysaccharide, pullulan polysaccharide and peach gum polysaccharide; The double-layer coated titanium dioxide is air flow crushed to obtain modified titanium dioxide.
7. The method for preparing modified titanium dioxide according to claim 6, characterized in that: In the step of dispersing titanium dioxide in water to obtain a titanium dioxide suspension, the concentration of titanium dioxide in the titanium dioxide suspension is 50 g / L to 100 g / L; the stirring speed of the dispersion is 800 rpm to 100 rpm, and the stirring time is 10 min to 15 min; and / or; In the steps of adding a weak base salt to the titanium dioxide suspension for stirring, adding an alkaline solution to promote the hydrolysis reaction of the weak base salt, and drying to obtain an inorganic material-coated titanium dioxide material, the weak base salt includes one or more of aluminum sulfate, aluminum chloride and alum; the alkaline solution includes one or more of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate solution, which can be a sodium hydroxide solution with a concentration of 1.2 mol / L to 1.5 mol / L, and the pH value of the alkaline solution can be 9 to 10; and / or; In the steps of adding a weak base salt to the titanium dioxide suspension for stirring, adding an alkaline solution to promote the hydrolysis reaction of the weak base salt, and drying to obtain an inorganic material-coated titanium dioxide material, the stirring speed is 2500 rpm to 5000 rpm, the stirring time is 30 min to 45 min; the drying temperature is 80° C. to 110° C.; and / or; In the step of placing the inorganic material coated titanium dioxide material in water, adding a second coating material, stirring and mixing, and drying to obtain a double-layer coated titanium dioxide, the stirring and mixing temperature is 50°C to 60°C, optionally, the stirring and mixing speed is 5000rpm to 6000rpm, optionally, the stirring and mixing time is 30min to 45min; the drying temperature is 80°C to 110°C.
8. A skin external preparation, characterized in that: The skin topical preparation comprises the modified titanium dioxide according to any one of claims 1 to 5, and the skin topical preparation comprises liquid foundation, air cushion, primer, sunscreen, liquid concealer, concealer, lipstick, lip glaze, liquid eyeliner, eyeliner pencil, eye shadow, blush or pressed powder.
9. The external skin preparation according to claim 8, characterized in that The foundation liquid comprises the following components in parts by weight: The modified titanium dioxide, 10 parts; and all based on 10 parts of the modified titanium dioxide: Emulsifier, 0.5-5 parts; oil, 8-30 parts; sunscreen, 5-15 parts; emulsifier, 2-10 parts; thickener, 0.2-2 parts; color powder, 1-5 parts; humectant, 5-20 parts; stabilizer, 0.2-2 parts; preservative, 0.2-2 parts.
10. The external skin preparation according to claim 9, characterized in that The foundation liquid comprises the following components in parts by weight: The modified titanium dioxide, 10 parts; and all based on 10 parts of the modified titanium dioxide: Polyglyceryl-4 isostearate, 0.5-2 parts; Cyclopentasiloxane, 5-20 parts; Phenyl trimethicone, 1-5 parts; Ethylhexyl methoxycinnamate, 5-20 parts; Cetyl PEG / PPG-10 / 1 dimethicone, 2-10 parts; C12-15 alcohol benzoate, 1-5 parts; Distearyl dimethylamine hectorite, 0.5-2 parts; nano-sized titanium dioxide, 0.5-3 parts; iron oxide, 0.5-3 parts; 1,3-butylene glycol, 2-10 parts; magnesium sulfate, 0.5-2 parts; phenoxyethanol, 0.5-2 parts; 1,2-hexanediol, 0.5-2 parts.
Citation Information
Cited By
Skin bionic powder as well as preparation method and application thereof
CN121622504A